The constructive membership problem for discrete two-generator subgroups of SL(2,R) - Kirschmer, Markus; Rüther, Marion G. (Journal of Algebra)
We describe a practical algorithm to solve the constructive membership problem for discrete two-generator subgroups of SL₂(R) or PSL₂(R). This algorithm has been implemented in Magma for groups defined over real algebraic number fields.
Keywords: Algebra and Number Theory